2001
DOI: 10.2144/01303pf01
|View full text |Cite
|
Sign up to set email alerts
|

Using a CCD Camera Imaging System as a Recording Device to Quantify Human DNA by Slot Blot Hybridization

Abstract: Slot blot hybridization of membrane-immobilized, single-stranded human DNA with the higher primate-specific alphoid probe D17Z1 is routinely used in forensic science to estimate the amount of DNA in biological samples. Typically, a chemiluminescent signal captured on film records the hybridization, and the quantity of the signal is related to the amount of immobilized DNA. Digital imaging using a cooled CCD camera offers an alternate non-film-based method for image acquisition with comparable sensitivity of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 1 publication
(3 reference statements)
0
16
0
Order By: Relevance
“…The other 9 cytokines were not changed when measured by ELISA, which may be due to the limitations of the cytokine antibody array. There is already a report demonstrating that a linear response between the chemiluminescent signal and quantity may not always exist, which may lead to the false results shown in the cytokine antibody array (23), so further verification experiments such as ELISA are necessary. CD30L is the ligand for CD30, which represents the newest member of the tumor necrosis factor receptor (TNF-R) family (24).…”
Section: Discussionmentioning
confidence: 99%
“…The other 9 cytokines were not changed when measured by ELISA, which may be due to the limitations of the cytokine antibody array. There is already a report demonstrating that a linear response between the chemiluminescent signal and quantity may not always exist, which may lead to the false results shown in the cytokine antibody array (23), so further verification experiments such as ELISA are necessary. CD30L is the ligand for CD30, which represents the newest member of the tumor necrosis factor receptor (TNF-R) family (24).…”
Section: Discussionmentioning
confidence: 99%
“…The methodology is based on digital imaging using a cooled CCD camera that has a theoretically wider linear dynamic range than standard film-based imaging (17,18). However, even when signals are within the detection limit of the imaging system, data points do not always conform to the expected linear trend (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One prominent point of cross-talk between adhesion and growth factors involves the serine/threonine kinase, extracellular signal-regulated kinase (Erk). 2 Several reports have shown that growth factor-mediated Erk signaling is enhanced among cells adhered to extracellular matrix (ECM) proteins (2,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In fact, this adhesion-mediated enhancement of Erk signaling plays a crucial role in cell cycle regulation.…”
mentioning
confidence: 99%
“…The standard curve is then used to calculate the DNA quantity in specimens from chemiluminescence intensities. This method is more objective than the analysis based on visual evaluation alone (5). QuantiBlot is a time-consuming and tedious procedure.…”
Section: Part I Comparison Of Dna Quantitation Techniques For Forensmentioning
confidence: 99%